Multi-scale patterns of habitat use by wild boar in the Monte Desert of Argentina - Cuevas, Maria Fernanda (2013)
A large number of protected areas worldwide have been impacted by biological invasions, threatening the biodiversity they aim to protect. The wild boar (Sus scrofa) is one of the most threatening invasive species in Argentina, already occupying many ecoregions, including the central Monte Desert. However, there are no studies regarding the use that wild boars make of this invaded biome and what factors (climate or landscape) determine or contribute to the establishment of this species. The objectives of this study were to assess habitat use of the wild boar at spatial and temporal scales in the central Monte Desert, and to assess if climatic factors influence its abundance. Our results show that, at habitat-level the wild boar exhibited preferences for a particular habitat (Larrea shrubland) for feeding. At microhabitat-level, we found a positive association between herb cover and wild boar presence. In addition, we found a strong and positive association between the number of days with low temperatures and the number of wild boar signs registered. Therefore, we consider that in the central Monte Desert, habitat selection by wild boars is most likely determined by a maximization of food intake and a minimization of exposure to high temperature.